Tracing genetic differentiation of Chinese Mongolian sheep using microsatellites - Zhong, T.; Han Jianlin; Guo, J.; Zhao, Q.J.; Fu, B.L.; Pu, Y.B.; He, X.H.; Jeon, J.T.; Guan, Wei-Jun; Ma, Y.H. (Wiley, 2011)
The genetic consequences of population differentiation and isolation have been the subject of conservation biology. In this study, we analysed the genetic diversity and structure of Mongolian sheep in China. These animals belong to a traditional local breed with high production, extensive adaption, early maturity and roughage resistance. For this purpose, 26 microsatellites were genotyped for five Mongolian sheep populations. The Bayesian clustering indicated five clusters as the most probable genetic structure of the populations investigated. In addition, a clear genetic structure was revealed in three populations distributed at large geographical scales, while the other cluster encompassed UQ and HLBR sheep that displayed no clear differentiation, probably due to their close and small geographical distributions. Overall, our results are helpful in understanding the interplay of population dynamics in these close genetic lineages of Mongolian sheep.